Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan Keripik Singkong Aneka Rasa di Desa Paron Ngawi - Agna Virlia Andarista; Siti Zazak Soraya (Universitas Djuanda Bogor, 2022)
Paron Ngawi village has many lands that can be used as agricultural and plantation facilities, which often generate income and even become the main occupation of the community, one of which is cassava. The sales of cassava have not been able to meet their daily needs because the price is relatively cheap. Therefore, there needs to be innovation regarding cassava processing so that it has a high selling value. This community service activity aimed to increase the economic value of cassava into cassava chips with various flavors. The method used in this service is an asset- based community development (ABCD) approach by involving several homemakers in Paron Ngawi Village. The existence of this cassava chip processing training is expected to improve understanding, skills and impact the high interest of buyers.